Measurement of PTHrP, PTHR1, and CaSR expression levels in tissues of sea bream (Sparus aurata) using quantitative PCR - Hang, X. M. (2014)
A quantitative PCR (Q-PCR) method has been established to measure the mRNA expression levels of parathyroid hormone–related protein (PTHrP), parathyroid hormone receptor type 1 (PTHR1), and calcium-sensing receptor (CaSR) in sea bream (Sparus aurata), using the housekeeping gene, - actin, as endogenous control. TaqMan primers and probes were designed using the Primer Express program, according to the published/unpublished sequences of the three target genes and -actin of sea bream. Different tissues including gill, kidney, duodenum, hindgut, rectum, liver, heart, brain, pituitary, skin, muscle, and gonad were removed and immediately snap-frozen from three juvenile sea bream (100–150 g) cultured in sea water. The mRNAs were extracted and reverse-transcribed into cDNAs, which were subsequently examined by the ABI 5700 system using an optimized Q-PCR method. Triplicate measures of each sample indicated consistency of the technique. However, the mRNA expression levels for each transcript in these tissues were variable between fish and also relatively low. Nevertheless, this methodology can be used in the future studies of factors that may alter gene expression in these tissues.